Kesediaan Menggunakan Telemedicine pada Mahasiswa Farmasi di Daerah Istimewa Yogyakarta - Autsan Dwi Banowati; Dyah Ayu Puspandari; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
The delivery of medical services using telecommunications technology is known as telemedicine. Pharmacists are required to perform key aspects of telemedicine and telepharmacy, which are vital components of healthcare. This study set out to identify sociodemographic characteristics, evaluate perceived knowledge levels, perceptions of telemedicine, and pharmacy students' willingness to use telemedicine, as well as identify the variables that affect these perceptions. To assess perceived levels of knowledge, perceptions, and desire to use telemedicine, this study employed a cross-sectional survey approach. Google Forms was used to retrieve the data. A convenience sample of 422 respondents, who are current undergraduate pharmacy students and pharmacists at UII, UAD, UGM, USD, and UMY, was acquired for the study sample. The supervisor has rendered an expert opinion with face validity. The knowledge, perception, and readiness to utilize the telemedicine questionnaire underwent Cronbach's Alpha reliability test, and the results were 0.956 with an internal consistency score of 0.825. A descriptive and statistical Chi-square test was used for the analysis. According to the study's findings, 441 students were willing to complete the questionnaire. The student academic year factors, with P-values of 0.012 and 0.000 (0.05), had the greatest influence on knowledge and perception levels. Knowledge and perception levels were correlated with the desire to use telemedicine, with a P-value of 0.000 (0.05). The findings indicate that most respondents had a favorable opinion of telemedicine. Respondents who have never used telemedicine have an interest in using it in the future.